Status Gizi Dan Perkembangan Motorik Kasar Pada Balita Usia 6 - 12 Bulan Di Posyandu Dusun Kedungbendo Desa Gemekan Kecamatan Sooko Kabupaten Mojokerto - Wulia Susanti (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Nutritional status is a state body as a result of food consumption and use of nutrients. If things are not promptly corrected will certainly affect the nutritional status and child development. The study aims to determine the relationship between nutritional status with gross motor development of toddlers ages 6-12 months. Correlation studies using designs with a population of all children aged 6-12 months with sanpling that meets the inclusion criteria, amounting to a total of 36 infants by using sampling. The results obtained under five nutritional status over 8.3% with gross motor development either. Nutritional status of infants less 25% with less gross motor development. The results of test calculations with the Spearman Rank correlation value 569 obtained a significant correlation between nutritional status and gross motor development of toddlers ages 6-12 months. From these results it can be concluded that the infants in the hamlet posyandu Kedungbendo most nutritional status and the lack of gross motor development is not optimal. The better the nutritional status of the development of gross motor and the less the optimal nutritional status is more gross motor development is not optimal. To improve the nutritional status of the mother is expected to make efforts to provide food to the food consumption pattern and the right, according to the needs of toddlers. To enhance gross motor development toddlers ages 6-12 months then the mother is expected to perform stimulation and exercise in young children are expected to stimulate the child to perform a given movement.